Pedestrian walkability and satisfaction in Kuala Lumpur City Center, Malaysia - Mansouri, Mahsa (2014)
According to Kuala Lumpur Structure Plan 2020, one of the goals of the Ninth Malaysian Plan (RMK9) is to increase the economy through sustainable tourism. One of the characteristics of sustainable tourism is the ability to provide an interesting walking experience and efficient networks for pedestrians to move from one place to another. So,considering tourists’ satisfaction and expectation while walking could assist in making the city of Kuala Lumpur into an attractive international tourist destination. The aim of this study is to examine the accessibility, connectivity and continuity of pedestrian networks that are affecting tourists’ satisfaction while walking in the historic district of the city centre of Kuala Lumpur. Since, pedestrians in the city are facing with difficulty in getting to their destinations due to poor walkways accessibility, linkage, continuity and exiting obstructions along paths, encouraging walking through better pedestrian environment can optimize the quality of sidewalks and help building active communities. This study adopted a quantitative approach in the data collection and data analysis. Gate observation and Space Syntax analysis were conducted to evaluate features of existing walkways in terms of connectivity and accessibility. Gate observation and Space Syntax were used to examine pedestrian movement rate by identifying pedestrian intensity and integration value of networks to determine the degree of connectivity. Moreover, questionnaire survey was used to examine the tourists’ expectation and satisfaction of walkways in the city center of Kuala Lumpur to support tourists’ walking experience. The study focuses on two areas with different historical attractions and shopping centres. For questionnaire survey, 330 tourists randomly selected to answer the questions on pedestrian accessibility, connectivity and continuity. These multiple data sources are gathered and analyzed to form the findings. This study has revealed that the pedestrians observed in the study area do not orient their movement according to the spatial characteristics of the surrounding street, as it is more related to land uses and other attractors than connectivity level of walkways. In other words, urban activities and land uses do obviously increase places of attraction and generate traffic congestion. Moreover, the results of the questionnaire survey have showed that tourists’ satisfaction is related to walkways characteristics considerably. Among all parameters, the availability of attractive places to visit, interesting activities to get involved while walking and walkways’ availability on most of the streets are the most important factors for tourists, although gained the least level of satisfaction. Therefore, this necessitates the importance of land use in enhancing tourists’ walking experience in the historical district of Kuala Lumpur. Therefore, level of pedestrian accessibility, connectivity and continuity improvement in the historical district of Kuala Lumpur should be implemented by integrating them with the land uses through promotion of mixed-use development especially along the river front area and also where the office uses are dominant needs to be reconsidered. The findings of the study are valuable for planners and architects to provide good quality pedestrian network for Kuala Lumpur and other cities in Malaysia. They support the need for a walkable city that can attract more tourists and visitors.